Rosiglitazone use and post-discontinuation glycaemic control in two European countries, 2000–2010. Issue 9 (24th September 2013) - Ehrenstein, V; Hernandez, R K; Ulrichsen, S P; Rungby, J; Lash, T L; Riis, A H; Li, L; Sørensen, H T; Jick, S S
Abstract : Objectives: To evaluate the impact of risk minimisation policies on the use of rosiglitazone-containing products and on glycaemic control among patients in Denmark and the UK. Design, setting and participants: We used population-based data from the Aarhus University Prescription Database (AUPD) in northern Denmark and from the General Practice Research Database (GPRD) in the UK. Main outcome measures: We examined the use of rosiglitazone during its entire period of availability on the European market (2000–2010) and evaluated changes in the glycated haemoglobin (HbA1c ) and fasting plasma glucose (FPG) levels among patients discontinuing this drug. Results: During 2000–2010, 2321 patients with records in AUPD used rosiglitazone in northern Denmark and 25 428 patients with records in GPRD used it in the UK. The proportion of rosiglitazone users among all users of oral hypoglycaemic agents peaked at 4% in AUPD and at 15% in GPRD in May 2007, the month of publication of a meta-analysis showing increased cardiovascular morbidity associated with rosiglitazone use. 12 months after discontinuation of rosiglitazone-containing products, the mean change in HbA1c was −0.16% (95% CI −3.4% to 3.1%) in northern Denmark and −0.17% (95% CI −0.21% to 0.13%) in the UK. The corresponding mean changes in FPG were 0.01 mmol/L (95% CI −7.3 to 7.3 mmol/L) and 0.03 mmol/L (95% CI −0.22 to 0.28 mmol/L). Conclusions: Publication of evidence concerning the potential cardiovascular risks of rosiglitazone was associated with an irreversible decline in the use of rosiglitazone-containing products in Denmark and the UK. The mean changes in HbA1c and FPG after drug discontinuation were slight.